Analisis Bibliometrik Terhadap Penerapan Penggunaan Software Geogebra Pada Pembelajaran Geometri di Sekolah Menengah - Sudrajat, Sudrajat (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2025)
The use of GeoGebra as an interactive learning medium in geometry has become a major focus in various mathematics education studies. GeoGebra allows dynamic visualization of geometric objects and supports student engagement in understanding concepts more deeply. As the number of publications discussing the use of GeoGebra in geometry learning at the secondary school level increases, a comprehensive review is needed to identify trends, focus directions, and open research gaps. Therefore, this study aims to identify and map trends and research focuses on the use of GeoGebra in geometry learning in secondary schools through a descriptive bibliometric approach. Data in this study were obtained from the Google Scholar database with a total of 480 published articles that have been selected through the stages of identification, screening, eligibility, and inclusion. The results of the analysis show that the publication trend increased significantly in the period 2020–2025, with the highest citation peak occurring in 2022, namely 840 citations. The most dominant journals covering this topic are the Rafflesia Journal of Mathematics Education and the Cendekia Journal. The main focus of the research is divided into six large groups: GeoGebra; geometry; junior high school students; mathematics learning in secondary schools; application of the discovery model; and studies of algebra and problem solving. These findings not only provide a comprehensive overview of the development of GeoGebra research but also reveal potential new themes that can be developed in further studies.